2021
DOI: 10.1093/humrep/deab126.022
|View full text |Cite
|
Sign up to set email alerts
|

O-113 Effectiveness and treatment cost of assisted reproduction technology for women stimulated by gonadotropin in France: A cohort study using the National Health Database

Abstract: Study question How effective is Assisted Reproduction Technology (ART) in terms of cumulative live birth rate (CLBR) in France, depending on the gonadotropin used? Summary answer Among 214,539 stimulations, originator follitropin-alfa was associated with significantly higher CLBR when compared to Highly Purified-Human Menopausal Gonadotropin (HP-HMG) and biosimilars. What is k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…[ 15 18 ] An analysis of the French National Health System (SNDS) database showed that reference r-hFSH-alfa was associated with significantly higher cumulative LBR than highly purified menotropin or r-hFSH-alfa biosimilars among 214,539 stimulations. [ 27 ] However, findings of this study are in contrast to a previously published literature that reported no significant difference in LBR among those treated by originator or its biosimilar, suggestive of equivalent clinical efficacy. [ 21 28 ] According to Mastrangeli et al ., differences in the LBR can be explained by differences in structural profiles and manufacturing processes in the biosimilar and reference products, thereby influencing FSH receptor activation and therefore biological activity.…”
Section: Discussioncontrasting
confidence: 99%
“…[ 15 18 ] An analysis of the French National Health System (SNDS) database showed that reference r-hFSH-alfa was associated with significantly higher cumulative LBR than highly purified menotropin or r-hFSH-alfa biosimilars among 214,539 stimulations. [ 27 ] However, findings of this study are in contrast to a previously published literature that reported no significant difference in LBR among those treated by originator or its biosimilar, suggestive of equivalent clinical efficacy. [ 21 28 ] According to Mastrangeli et al ., differences in the LBR can be explained by differences in structural profiles and manufacturing processes in the biosimilar and reference products, thereby influencing FSH receptor activation and therefore biological activity.…”
Section: Discussioncontrasting
confidence: 99%
“…The rapidly growing use and validation of large, computerized medical records and related databases (e.g., health insurance or national registries) have played a major part in changing the perceptions of observational data among researchers and clinicians and should be also taken into account [ 57 ]. For example, a non-interventional study based on the French National Health System (SNDS) database demonstrated that among 214,539 stimulations, reference r- hFSH-alfa was associated with significantly higher cumulative live birth rates compared with hMG-HP and r-hFSH-alfa biosimilars [ 58 ].…”
Section: Discussionmentioning
confidence: 99%